2008
DOI: 10.1002/jsfa.3184
|View full text |Cite
|
Sign up to set email alerts
|

Hemagglutinating activity and corresponding putative sequence identity from Curcuma aromatica rhizome

Abstract: BACKGROUND: Curcuma aromatica is a medicinal plant belonging to the Zingiberaceae family with an incomplete genome sequence. It has been reported that extract from the rhizome of this plant contains haemagglutinating activity. In this study the profile of fractions containing hemagglutinating activity is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…A mannose binding lectin with a molecular mass of 13.4 kDa was also isolated from C. zedoary [ 39 ]. In addition, six homologous lectin proteins of various molecular masses (8.84-32.8 kDa) were found in C. aromatica [ 40 ]. Most of them are mannose binding lectins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A mannose binding lectin with a molecular mass of 13.4 kDa was also isolated from C. zedoary [ 39 ]. In addition, six homologous lectin proteins of various molecular masses (8.84-32.8 kDa) were found in C. aromatica [ 40 ]. Most of them are mannose binding lectins.…”
Section: Resultsmentioning
confidence: 99%
“…Most plant cysteine proteases belong to the papain and legumain families. Recently this enzyme family was reported from three members of the ginger family, in C. longa [ 43 ], C. aromatica [ 40 ] and Z. offinale Roscoe [ 44 ], and this ginger protease is used as a food improver and anti-inflammatory agent. Founding cysteine protease in four members of Zingiberaceae plant, C. comosa, C. longa, C. aromatica and Z. offinale at difference molecular weigh and pI position, the ginger cysteine protease might be a protein marker to classify specific species in this family in the future.…”
Section: Resultsmentioning
confidence: 99%
“…A mannose-binding lectin from the Zingiberaceae member, Curcuma zedoaria Rosc., has been identified and found to have sequence similarity to a mannose-binding lectin from the broad-leaved helleborine orchid, Epipactis helleborine (L) Crantz (Asparageles: Orchidaceae) [27]. In the related Curcuma aromatica, six putative proteins from nine bands derived from a rhizome preparation showed similarity with other lectin sequences [28], whilst a study on the hemagglutinating activity of Curcuma plants found hemagglutinating activity in the species of this study, Khamindum or Curcuma amarissima [29].…”
Section: Introductionmentioning
confidence: 94%
“…Protein was isolated from the rhizomes using the procedure described by Tiptara [22] and Samarkina [23] with some modification. Briefly, the rhizomes were peeled, minced into small cubes (about 5×5×5 mm), and soaked in 20 mM Tris-HCl buffer pH 7.2, containing 0.15 M NaCl, with care to cause minimal oxidation by air exposure.…”
Section: Extraction Of Protein From the Rhizomes Of Z Ottensiimentioning
confidence: 99%